Kitagawa Utamaro's 'Standing Courtesan Reading a Letter': the collaborative conservation of a master scroll painting and its silk mount. Issue 1 (2nd January 2021) - Kusunoki, Kyoko; Pullan, Monique; Harrison, Anna; Oka, Iwataro-Yasuhiro; Sugiyama, Keisuke; Cartwright, Caroline
Abstract: In 2014 the British Museum acquired a little-known masterpiece painting, 'Standing Courtesan Reading a Letter', by the Japanese artist Kitagawa Utamaro (1753?–1806). Originally a hanging scroll, the painting arrived with its top and bottom mounting silks ( joge ) missing, but the inner mounting silks ( chūberi and ichimonji ) were still intact. The inner middle border silks—the chūberi —were constructed from recycled high-quality kimono silk with couched metal thread embroidery, which was partly detached and unravelled. This article accounts for the conservation and remounting of the painting, including the retention and conservation of the middle border silks, and discusses the decision-making processes regarding the re-use and replacement of the mounting silk from the perspective of curators and conservators from Japan and the UK. It also reports on how the project was undertaken as part of the Collaborative Project for the Conservation of Japanese Paintings in the British Museum, with BM conservators working together with scroll mounting conservators from the Association for Conservation of National Treasures (ACNT) of Japan, supported by the Sumitomo Foundation.